(untitled) (The Review of Diabetic Studies, 2025)
This research aims to study the impact of cooperation between the Saudi Red Crescent and Civil Defense in confronting and managing major crises and disasters. The study was based on the descriptive analytical approach, and included a sample of (200) individuals working in the Saudi Red Crescent. The questionnaire was used as the main tool for data collection, and its topics covered the areas of coordination, joint plans, training, resource distribution, and job satisfaction. The results showed that the level of cooperation between the two parties contributes significantly to the speed of response, reducing human losses, and enhancing the efficiency of crisis management. It also enhances community confidence in the ability of the relevant agencies to confront disasters effectively. The study recommends increasing joint training and developing communication and coordination mechanisms to achieve the highest levels of efficiency in emergency response.